Odpowiedzi

2010-02-08T19:10:54+01:00
B)
3x-4y=7 / *2
-2x+3y=-4 / *3

6x-8y=14
-6x +9y = -12

y= 2
6x - 8*2= 14

6x - 16 = 14
6x= 30 / 6

x= 5
y=2

2 5 2
2010-02-08T19:14:48+01:00
A).
y=2x+2
2x-3(2x+2)=6
y=2x+2
2x-6x-6=6
y=2x+2
-4x=6+6
-4x=12 |:(-4)
x = -3
y=2(-3)+2
x=-3
y=-6+2
x=-3
y=-4
b).
3x-4y=7 |*2
-2x+3y=-4 |*3
6x-8y=14
-6x+9y=-12
6x-8y-6x+9y=14-12
y=2
3x-4*2=7
y=2
3x-8=7
y=2
3x=15 |:3
y=2
x=5
;))


Najlepsza Odpowiedź!
2010-02-08T19:19:50+01:00
A)
y=2x+2
2x-3y=6

y=2x+2
2x-3*(2x+2)=6

y=2x+2
2x-6x-6=6

y=2x+2
2x-6x=6 +6

y=2x+2
-4x=12 / :(-4)

y=2x+2
x=-3

y=2*(-3)+2
x=-3

y=-6+2
x=-3

y=-4
x=-3

b)
3x-4y=7 / *2
-2x+3y=-4 / *3

6x-8y = 14
-6x+9y = -12 dodajemy jedno do drugiego i x się zeruje
y = 2

3x-4y=7 / *3
-2x+3y=-4 / *4

9x-12y =21
-8x+12y =-16 dodajemy jedno do drugiego i y się zeruje
x = 5


x=5
y=2